Criminal Law Treats for Online Gambling Performers: Investment Fraud Modes - Iqbal Kamalludin; Heris Suhendar; Bunga Desyana Pratami; 'Alamul Yaqin; Nur Afifah (Faculty of Law, Maranatha Christian University, 2022)
Since 2018 to July 2022, the Ministry of Communication and Information has cut off access to 534,138 gambling content on various digital platforms. This very high number will continue to grow. One of the reasons for the rise of online gambling content is the mode that is used, namely the